An Indifference Approach to Profit-Volume Analysis. - Edwards, Edgar O.; Johnson, L. Todd; Strawser, Robert H. (The Accounting Review, 1974)
Abstract This article studies an indifference approach to profit-volume analysis. Students of economics encounter indifference curves, in analyzing consumer behavior, welfare and international trade. Employment of this tool in accounting as well should prove practicable even at the introductory as it is likely that enrollees in introductory accounting courses either will have completed introductory economics courses or will be concurrently enrolled in them. Thus, the primary concern need not be centered around a discussion of indifference curves themselves but rather on their application to traditional accounting topics. The family of indifference curves is constructed as follows. The authors of this article assume a firm knows its average variable costs associated with each level of output.